Calidad de rubores cosméticos comercializados en emporio albarracín, trujillo - 2016” - Cruz Flores, Melisa Isabel (2017)
The present field work had the purpose to determine the quality in cosmetic flushes commercialized in emporium Albarracín, Trujillo - 2016, a total of 20 flushing samples were processed in Albarracín emporium. In the determination of organoleptic characteristics, we evaluated: presentation, odor, appearance and adhesion; Without showing acceptable percentages in these parameters. As for the physical-chemical determination, a percentage of volatile matter was presented, being the highest of 0.23% in the Thais Garden sample and the lowest of 0% in the RW sample. In the microbiological analysis of mesophilic aerobes a percentage of 5% <100UFC was obtained, in the sample BELLE SPA and 95% presented absence. In the analysis of enterobacteria (Escherichia coli) a 75% absence was obtained and 25% had <100UFC; There was absence of Pseudomona aeruginosa and Staphylococcus aureus in all the samples studied, and finally in 3 different marks showed growth of fungi and yeasts